Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I need to integrate $$\int { \sqrt{x^2-a^2} \over x } \mathrm dx $$ using substition, and show it equals $$ \sqrt{x^2 - a^2} - a(\operatorname{arcsec} ({x\over a })) +c $$

I've tried $x=a\sin t$ but I couldn't finish it out.

Thank in advance for any help.

share|improve this question
    
Where did you encounter problems? –  Zhoe Nov 21 '13 at 13:34
    
Using $x= asint$ leaves $sin^2t - 1$ under the square root, which can't be replaced by $cos^2t$ as is normal in problems of this kind. –  Crockett Nov 21 '13 at 13:37
1  
Try $x=a \sec(t)$. –  N. S. Nov 21 '13 at 13:41
    
Have you tried $x=a\sec{u}$? –  David H Nov 21 '13 at 13:41
    
@CillianR It leaves $\sqrt{-\cos^2(t)}$. –  N. S. Nov 21 '13 at 13:41

2 Answers 2

up vote 7 down vote accepted

Use the substitution:

$$x = a \sec(\theta)\implies dx = a \sec\theta\tan\theta\,d\theta$$

And use the identity

$$\sec^2(\theta)-1 = \tan^2(\theta).$$ $\require{cancel}$ Then your integral becomes: $$\begin{align}\int { \sqrt{x^2-a^2} \over x } dx & = \int \dfrac{\sqrt{a^2\sec^2 \theta - a^2}(\cancel{a \sec\theta}\tan\theta \,d\theta) }{\cancel{a\sec\theta}}\, \\ \\ & = a\int \sqrt{\tan^2\theta}\, \tan\theta\,d\theta \\ \\ &= a\int \tan^2 \theta \,d\theta \\ \\ & = a\int (\sec^2 \theta - 1)\,d\theta \\ \\ & = a \int \sec^2 \theta \,d\theta - a\int d\theta\\ \\ & = a \tan\theta - a\theta + c\end{align}$$

Now, back substitute to get $$\sqrt{x^2 - a^2} - a\left(\operatorname{arcsec} \left({x\over a }\right)\right) +c$$

share|improve this answer
    
from an ipod during walking under rain +1 :-) –  Babak S. Nov 21 '13 at 14:59

Calculating this integral can be done in this way:

$$\int { \sqrt{x^2-a^2} \over x } dx =\int { x^2-a^2 \over x\sqrt{x^2-a^2} } dx= \int { x \over \sqrt{x^2-a^2} } dx-\int { a^2 \over x\sqrt{x^2-a^2} } dx =\sqrt{x^2-a^2}(+-)a\cdot\int {(\frac{x}{a})'\over \sqrt{1-(\frac{x}{a})^2)} } dx=\sqrt{x^2-a^2}(+-)a\cdot\arcsin(\frac{x}{a})+C.$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.